The Influence of Digitalization of Learning Media on the Reading Interest of Anugerah Abadi Pamulang Primary School Students - Aspari, Aspari; Prayudhi, Risa (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Reading is a very important activity in society, especially in the world of education at all levels. Apart from adding information, it is also to increase knowledge and broad thinking insights. In the current digital era for reading, you don't need to have to buy books or borrow books from the library, but by simply accessing sites that provide reading via a smart phone which almost all people on this earth have, then whoever he is will definitely find it easy to get the right reading. cool, including students and educators. The easier it is to obtain reading media through sites on the internet in digital form invites researchers to find out the influence of digitalization of learning media on the influence of students' reading interest when studying at home or at school. The research method used in this research is a descriptive survey method. The research sample taken consisted of 79 respondents who came from students in grades 4, 5 and 6 of elementary school. Data collection instruments using questionnaires, interviews, observation and documentation. Based on the results of research originating from questionnaires, it was found that 50.6% felt that their interest in reading had increased with the presence of digital learning media.